2018
DOI: 10.1080/15374416.2018.1466306
|View full text |Cite
|
Sign up to set email alerts
|

Laboratory and Self-Report Methods to Assess Reappraisal and Distraction in Youth

Abstract: Coping and emotion regulation are central features of risk and resilience in childhood and adolescence, but research on these constructs has relied on different methods of assessment. The current study aimed to bridge the gap between questionnaire and experimental methods of measuring secondary control coping strategies, specifically distraction and cognitive reappraisal, and examine associations with symptoms of anxiety and depression in youth. A community sample of 70 youth (ages 9-15) completed a novel expe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 44 publications
0
3
0
Order By: Relevance
“…However, older adults depend on crystallized intelligence rather than flexible processing (Labouvie‐Vief, 2009). It is important that emotion regulation strategy be assessed by self‐reported methods, which are natural and close to real‐life contexts than behavioral study in the laboratory (Aldao et al, 2010; Bettis et al, 2019). Difficulties in Emotion Regulation Scale (DERS) and Emotion Regulation Questionnaire (ERQ) are broadly used to assess emotion regulation strategy (Ma & Fang, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…However, older adults depend on crystallized intelligence rather than flexible processing (Labouvie‐Vief, 2009). It is important that emotion regulation strategy be assessed by self‐reported methods, which are natural and close to real‐life contexts than behavioral study in the laboratory (Aldao et al, 2010; Bettis et al, 2019). Difficulties in Emotion Regulation Scale (DERS) and Emotion Regulation Questionnaire (ERQ) are broadly used to assess emotion regulation strategy (Ma & Fang, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…The second section asked participants whether they often attempted to influence the negative emotions (selected in the previous section) and in the case of “Yes” response, they were guided to the third section. In the third section, the participants were provided with a list of strategies (including primary control, secondary control, disengagement, and involuntary engagement) that they often applied to control their emotions ( Bettis et al, 2019 ). Primary control strategies included problem-solving (“I tried to find proper solutions to take care of myself and my family”) and social sharing (“I tried to share my emotions and asking others for advice”), secondary control strategies included reappraisal (“I tried to think about a situation differently in order to change my mood”) and distraction (“I shifted my attention away from what was making me emotional”), disengagement included suppression (“I tried not to reflect an emotion I felt inside”), and involuntary engagement included rumination (“I repeatedly thought about the COVID-19 issues and could not stop thinking for a moment”) ( English et al, 2017 ).…”
Section: Methodsmentioning
confidence: 99%
“…Thus, it is possible that reappraisal protects against mental health problems through improved social functioning. However, it is also possible that a higher level of depressive symptoms may result in less successful reappraisal (Bettis et al, 2019 ). This notion is supported by a meta-analysis of 13 fMRI studies (mainly with adult participants) that found that depressed patients exhibit reduced activation in the cognitive control network during cognitive reappraisal tasks compared to healthy controls, which suggests that reappraisal may not be effective in depression (Picó-Pérez et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%